Strategi Kreatif dalam Film Lemantun Karya Wregas Bhanutedja - Reno Ryandra; Syaifuddin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
A program can be said to be successful if it can make the audience enjoy the show. Included also in the form of short films programs. To achieve that goal, creative strategies are one way to make a program more interesting. The purpose of this research is to find out the creative strategy of Lemantun a Short Film by Wregas Bhanutedja. With this research, we can find out what creative strategies Lemantun short film team used. The method in this study used a descriptive quantitative approach with interview and literacy techniques to obtain more accurate results. This study uses the post-positivism paradigm and uses the Herbert Zettl program strategy as a reference to analyze the data obtained. The results obtained are that Lemantun can convey the message that has been formed by the creative team to the audience, with a strategy that refers to the selection of names, selection of players, and the concept of the program.